On the study the radius of analyticity for Korteweg-de-Vries type systems with a weakly damping - Sadok Otmani; Aissa Bouharou; Khaled Zennir; Keltoum Bouhali; Abdelkader Moumen; Mohamed Bouye (AIMS Mathematics)
In the present paper, we considered a Korteweg-de Vries type system with weakly damping terms and initial data in the analytic Gevery spaces. The presence of tow functions $ c_1(x), c_2(x) $, called damping coefficients, made the system more interesting from an application point of view due to their great importance in physics. To start, by using the fixed point theorem in Banach space, we investigated the local well-posedness. Additionally, by employing an approximate conservation law, we extended this to be global in time, ensuring that the radius of analyticity of solutions remained uniformly bounded below by a fixed positive number for all time.